Tata Kelola Pemerintahan dalam Pengoptimalan Pemantauan dan Evaluasi Kinerja Penyelenggara Pelayanan Publik (PEKPPP) di Kecamatan Pabean Cantian Kota Surabaya - Maharani, Shinta Aurellia; Prathama, Ananta (IAI Nasional Laa Roiba Bogor, 2024)
Good and correct governance can be seen from governance that can make society prosperous and prosperous, including in terms of public services. Public services are essentially aimed at satisfying and adapting to the desires and needs of the community. In general, providing excellent service to the community is a manifestation of the duties of government officials as implementers of public services. Therefore, in the implementation of public services, both in sub-district and central agencies, it is necessary to carry out monitoring and evaluation. Cantian Pabean District is one of the regional government organizations in the city of Surabaya that provides public services in its area. The research method used in this research is descriptive research with collection techniques through observation and interviews. The focus of this research is focused on how to apply the principles of good governance in optimizing the fulfillment of supporting data from six aspects in the implementation of PEKPPP in the Cantian Pabean District based on the principles of Good Governance according to Sedarmayanti (2014: 5). The results of the research explain that the Cantian Customs District has implemented and implemented the principles of Good Governance which, when reviewed through PEKPPP, can be said to have fulfilled all existing principles, aspects and indicators.